SOCIAL ENTREPRENEURSHIP EDUCATION: PREPARING THE NEXT GENERATION OF ETHICAL ENTREPRENEURS - Zainal, Andri; Harahap, Khairunnisa; Budiarta, Kustoro; Hasibuan, Novita Indah (Universitas Negeri Medan, 2017)
Abstract The nature of entrepreneurship for youth is basically identical with the one that has been widely practiced by the adults. Extent literatures suggest that the concept of youth entrepreneurship lies in the social benefit of wealth creation through the application of innovative thinking and execution to meet customer needs, using one™s own labour, time and ideas. Several factors such as age, level of maturity and intellectual differentiation are also considered to differentiate the entrepreneurship pattern in between youth and adult entrepreneurs. Thus, two major points need to be taken into further consideration: how the entrepreneurship is taught and how it is learned. These initiatives will project significant contributions for the youth, not only providing them with sufficient knowledge and skills toward becoming the next world class business actors but also embedding them with moral and business ethics values in the establishment of the natural ethical entrepreneurs. Keywords: Business Ethics, Social Entrepreneurship, Social Entrepreneurship Education, Ethical Entrepreneurs